The Effectiveness of Granulation of Chitosan Placuna Placenta Shells on the Growth of the Leaves of the Plants of Apium Graveolens L. - Ariyanti Ariyanti; Eni Masruriati; Alfelina Prasista Hapsari; Arin Widya Nuari (Indonesian Journal of Global Health Research, 2021)
The use of chitosan as fertilizer can increase nitrogen. Therefore, to improve the quality of the production of Apium graveolens L. with solid waste chitosan granules from Placuna placenta Shells on the growth of Apium graveolens L. plants in polybags. Pre-experimental design in the form of the post-test only controlled group design which was divided into 3 treatment groups, namely 5% chitosan concentration; 15% and 20% and the control group, namely positive control (x) and negative control by measuring the growth of Apium graveolens L. capillaries including plant height (cm), number of leaves (strands), and number of fruit. Data were analyzed using one way ANOVA test. Placuna placenta Shell chitosan granule fertilizer affects plant height and number of leaves on Apium graveolens L.. The optimal concentration of Placuna placenta Shell chitosan granules as fertilizer for Apium graveolens L. plant which produces the highest value in all measurement parameters is 20% concentration. Chitosan granules from Placuna placenta Shells can be used as an alternative to organic fertilizer for Apium graveolens L. with an effective concentration of 20%.